Mercy – a Central Virtue in Animal Ethics - Borgdorf, Leon (Journal of applied animal ethics research, 2025)
In ethical debates regarding modern technologies in livestock production, virtue ethics plays a subordinate role. We address this issue by providing a virtue ethical framework centered on mercy. First, we define mercy as a virtue, which applies when the moral agent can harm someone vulnerable and refrains from doing so. Second, we link mercy to empathic concern, which we argue to be crucial for virtue because it informs moral agents about pain in others and inhibits them from harming others. Drawing on an existing argument from military ethics about the viciousness of unlearning empathy in the case of soldiers learning to kill, we problematize animal slaughter. Third, we argue that a virtuous society promotes eudaimonia in its citizens and therefore should not require them to become merciless. We conclude that societies should not endorse practices that cultivate mercilessness, but encourage practices that increase mercy towards others, including farmed animals.